Vonoprazan and Helicobacter pylori Treatment: A Lesson From Japan or a Limited Geographic Phenomenon? - Abadi, Amin Talebi Bezmin; Ierardi, Enzo (Frontiers in Pharmacology, 2019)
Within a short time after the discovery of H. pylori, its critical role in many gastroduodenal disorders had been described. Many in vitro and in vivo data have proven that infection should be treated in order to avoid that the lasting colonization may lead to problematic gastroduodenal diseases. Probiotics, preventive and therapeutic vaccines and antibiotic therapy are the main practically proposed options to cure disorders. Twenty-five years ago, triple therapy including a traditional proton pump (PPI) inhibitor and two antibiotics (amoxicillin and clarithromycin or metronidazole) were defined as a best formulation in the therapy of H. pylori infection. With the strongly decreased effectiveness of this scheme, many empirical therapeutic regimens have been developed. However, the prevalence of resistance is growing worldwide and shows important geographic differences and even the most recent and effective regimens show some critical points. In this review, we attempted to open a new window to overcome the problem of antibiotic resistance to H. pylori. Indeed, we focused our attention on the possibility that the time of conventional PPI may be ending and vonoprazan is initiating a new era characterized by an improved therapeutic chance for H. pylori infection. In other words, switching to vonoprazan as novel acid blocker can initiate a new era for of H. pylori treatment with an unexpected reassessment of triple therapy, at least in regions with low rate of clarithromycin resistance.